2009
DOI: 10.1158/1541-7786.mcr-08-0409
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of DNA Repair in Stem and Nonstem Glioma Cell Cultures

Abstract: It has been reported that cancer stem cells may contribute to glioma radioresistance through preferential activation of the DNA damage checkpoint response and an increase in DNA repair capacity. We have examined DNA repair in five stem and nonstem glioma cell lines. The population doubling time was significantly increased in stem compared with nonstem cells, and enhanced activation of Chk1 and Chk2 kinases was observed in untreated CD133 + compared with CD133 À cells. Neither DNA base excision or single-strand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
161
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 172 publications
(165 citation statements)
references
References 34 publications
2
161
0
2
Order By: Relevance
“…25 In these conditions, cells adopted a round morphology and formed spheres after several days (data not shown), in parallel to increased MerTK expression (Figure 4a). Interestingly, other GBM cell lines growing under stem cell culture conditions either died (data not shown) or showed adherent features with an elongated morphology (Supplementary Figure 4a).…”
Section: Mertk Is Overexpressed In Malignant Gliomasmentioning
confidence: 81%
“…25 In these conditions, cells adopted a round morphology and formed spheres after several days (data not shown), in parallel to increased MerTK expression (Figure 4a). Interestingly, other GBM cell lines growing under stem cell culture conditions either died (data not shown) or showed adherent features with an elongated morphology (Supplementary Figure 4a).…”
Section: Mertk Is Overexpressed In Malignant Gliomasmentioning
confidence: 81%
“…However, analysis of proliferation over an 80-day period showed radiosensitization after either one, two or three KU60019 plus IR treatments (Figs. 5e [4][5][6] and f 4,5 ; Table 1). Previous studies have identified subgroups of GB based on genetic and epigenetic variations of a number of genes including H3F3A and IDH1.…”
Section: Efficacy On Adult and Pediatric Tumorsmentioning
confidence: 99%
“…2 GIC lines deriving from adult GB have been previously described. 2,6 The pediatric GIC lines 239/12 and 170/OG have been obtained from surgical resection of an anaplastic astrocytoma (WHO grade III) in a 14-year-old male and a GB (WHO grade IV) in a 12-year-old male, respectively. Both patients died because of the tumors within 3 years from the diagnosis.…”
Section: Cell Lines and Culture Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations characterizing subpopulations of aberrant stem cells have shown efficient DSB repair through various DNA damage markers, but no specific pathways have been identified to explain the increased survival (7). Recent reports also provided evidence for differences in radiosensitivity between subpopulations of glioma-initiating cells (8)(9)(10), suggesting disparity in DNA repair efficiency. Whether DNA repair is a major mechanism of radioresistance in glioma-initiating cells remains controversial.…”
Section: Introductionmentioning
confidence: 99%